2023
DOI: 10.19028/jtep.011.2.240-252
|View full text |Cite
|
Sign up to set email alerts
|

Does a Freeze-thaw Pretreatment Enhance the Quality of Dried Foods? A Meta-Analysis

Tri Yulni,
Wendianing Putri Luketsi Luketsi,
Waqif Agusta
et al.

Abstract: Based on the results of several studies, it's questionable if freeze-thaw pretreatment can improve dried product qualities. To answer this question, a meta-analysis was conducted to determine the effect of freeze-thaw pretreatment on the quality of dried products. This research aimed to assess the impact of freeze-thaw pretreatment on the quality of dried plant-based foods. The data was sourced from the Scopus database, and the selection criteria were based on the PRISMA protocol. All meta-analysis calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… Kurniasari et al (2022) investigated the bioactivity of ginger after undergoing different drying methods and found that the phenolic and flavonoid content, 6-gingerol concentration, and antioxidant activity varied depending on the method used. In another study, Yulni et al (2023) explored the effects of freeze-thaw pretreatment on plant-based food products and found that the TPC and color were decreased, whereas total flavonoid content (TFC) was increased. In light of these studies, our research focuses on the impact of osmotic pretreatment on the qualities of dried fruit.…”
Section: Introductionmentioning
confidence: 99%
“… Kurniasari et al (2022) investigated the bioactivity of ginger after undergoing different drying methods and found that the phenolic and flavonoid content, 6-gingerol concentration, and antioxidant activity varied depending on the method used. In another study, Yulni et al (2023) explored the effects of freeze-thaw pretreatment on plant-based food products and found that the TPC and color were decreased, whereas total flavonoid content (TFC) was increased. In light of these studies, our research focuses on the impact of osmotic pretreatment on the qualities of dried fruit.…”
Section: Introductionmentioning
confidence: 99%